The Influence of Organizational Culture and Burnout in Improving Employee Performance at the Syaamil Group - Nurikhsan, Yuniarti; Dian Indiyati (Cita konsultindo, 2025)
The competitive business environment necessitates organizations to optimize employee performance as a key driver of success. This study examines the influence of organizational culture and burnout on employee performance at Syaamil Group, a company grounded in Islamic values. Organizational culture, represented by the MIRACLE framework, serves as a cornerstone for fostering employee engagement and alignment with corporate goals. Conversely, burnout, characterized by emotional exhaustion, depersonalization, and inefficacy, has emerged as a critical factor undermining productivity. This research uses a quantitative approach, utilizing a survey method with 200 employees determined based on the Slovin sample formula. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was applied to analyze the relationships between organizational culture, burnout, and employee performance. Results indicate that organizational culture positively and significantly influences employee performance, while burnout exerts a negative and significant impact. These findings highlight the importance of maintaining a robust organizational culture to mitigate the adverse effects of burnout and enhance overall performance. This study provides actionable insights for organizational leaders seeking to balance cultural reinforcement and employee well-being, offering a pathway to sustained productivity and resilience in competitive markets.